2011
DOI: 10.1111/j.1600-0765.2011.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis between the −2518MCP‐1(A/G) polymorphism and generalized aggressive periodontitis in a Chinese population

Abstract: The polymorphisms of -2518MCP-1 may play an important role in determining generalized aggressive periodontitis susceptibility in this cohort of Chinese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…14,25 The G allele frequency of MCP-1 -2518 A/G in our study was similar to other studies in Asian groups (42.5e66%), 17,26,27 but it was different with Caucasian, AfricaneAmerican and Hispanic groups (22e30%). 14,28,29 Our study reported that 42.5% of Taiwanese had allele G at MCP-1 -2518 and revealed there are different distributions of MCP-1 gene polymorphism among various ethnic groups which was consistent with the findings of IL-1 gene polymorphism.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…14,25 The G allele frequency of MCP-1 -2518 A/G in our study was similar to other studies in Asian groups (42.5e66%), 17,26,27 but it was different with Caucasian, AfricaneAmerican and Hispanic groups (22e30%). 14,28,29 Our study reported that 42.5% of Taiwanese had allele G at MCP-1 -2518 and revealed there are different distributions of MCP-1 gene polymorphism among various ethnic groups which was consistent with the findings of IL-1 gene polymorphism.…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of MCP-1 -2518 G genotype has been shown to be significantly lower in female patients with aggressive periodontitis compared to the female healthy group. 17 On the other hand, they found aggressive periodontitis female patients with MCP-1 -2518 A/A genotype had deeper probing depth than patients with MCP-1 -2518 A/G and G/G genotype. Moreover, confounding factors such as smoking habits, age, baseline parameters in the periodontal treatment can be important considerations for dentists to predict the outcomes of periodontal treatments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The incidences in different areas and different races are different, which may be influenced by ethnic differences of gene polymorphisms [30]. Lots of studies have investigated the importance of genetic polymorphisms (e.g., MCP-1, S100A8, IL-1 α , IL-1 β , and N-formyl peptide receptor) in aggressive periodontitis [31–34]. To the best knowledge of the authors, there are only two studies that have investigated the association between GC gene and periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte chemoattractant protein (MCP)‐1 is a CC chemokine (Melgarejo et al , ) that attracts monocytes to inflammatory areas and plays a crucial role in inflammatory response, both in acute and chronic inflammatory conditions (Samaan et al , ; O'Connor et al , ). Relatedly, MCP‐1 has been observed in a variety of tissues during inflammation‐associated disease progression, and likewise, periodontitis patients have exhibited high levels of MCP‐1 in GCF (Lee et al , ; Emingil et al , ; Kurtis et al , ; Pradeep et al , ; Thunell et al , ; Tymkiw et al , ; Gupta et al , ), in gingival tissue (Yu et al , ; Yu and Graves, ; Gemmell et al , ; Garlet et al , ), and in sera/plasma (Pradeep et al , ; Zhu et al , ; Anil et al , ; Gupta et al , ) compared with periodontally healthy (H) subjects. In addition to these results, correlation between GCF MCP‐1 and clinical parameters as attachment loss suggests that MCP‐1 plays an important role in the attraction of monocytes and in the enhancement of inflammatory signals in periodontitis pathogenesis (Zhu et al , ).…”
Section: Introductionmentioning
confidence: 99%